Minerales desarrollados en hormigones deteriorados por la reacción álcali-sílice (provincia de Córdoba) - Maiza, Pedro (1999)
Samples of four deteriorated concretes from pavements near Córdoba city were studied. The objet from this paper is to determine the cause of the damage, to identiíy reaction products and to evaluate deleterious aggregates. The samples were studied by means of X ray diffraction, SEM and EDAX. Zeolites and ettringite associated with calcite and portlandite were identified. The presence of zeolile allows to conclude that the damage was consequence of the development of the alkali-silica reaction. The secondary ettringite contributes to the concrete degradation.